Optimal mixed taxation, credit constraints and the timing of income tax reporting - Robin Boadway; Jean-Denis Garon; Louis Perrault (Université du Québec à Montréal, École des sciences de la gestion (ESG UQAM), Département des sciences économiques, 2018)
We study optimal income and commodity tax policy with credit-constrained lowincome households. Workers are assumed to receive an even flow of income during the tax year, but make tax payments or receive transfers at the end of the year. They use their disposable income to purchase multiple commodities over the year. We show that di↵erentiated subsidies on commodities can be optimal even if the Atkinson-Stiglitz Theorem conditions apply. When the optimal policy leaves low-income households with binding credit constraints, it is optimal to subsidize the good that is consumed in higher proportion by them. We show that this involves subsidizing more goods that fulfill basic needs, such as food or dwelling. The benefits of such subsidies have to be balanced with the costs of financing them, since unconstrained households also benefit from the rebate early in the fiscal year.
Keywords: 330